(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Objectives: To study overweight and obese children and adolescents in Iraq whom presented with and without acanthosis nigricans And the relationship between acanthosis nigricans with insulin resistance and cardiometabolic comorbidities Research paradigm: The research employs a case series with use of cross-sectional analyses. Patients: The main focus of the investigation are the demography of Iraq children. These children were studied from April 2021 through January,2025. The justification for their inclusion is the fact that they are found to be overweight and obese from one hospital. Main measures: The demographic, acanthosis nigricans status, anthropometric data, and biochemical results were the main items of analyses. Results: the study concentrated on a total of about 75 overweight and obese children in Iraq. Out of this number, 47 were boys representing (63%), Acanthosis nigricans (AN) was noticed in 41 of subjects (55%), and 23 that is (29%) got insulin resistance (IR). Adolescents of age between 12-18 years were more than children of 5-11 years of age to have obtained AN (25/40) that is, [62%] vs. 16/35 that is [46%]; P<0.001) as well as IR (15/40 [38%] vs. 9/35 [26%]; P=0.005). Compared with overweight children, those who obese were more likely to have AN (34/59 [60%] vs. 7/16 [43%]; P=0.006) and IR (21/59 [36%] vs. 3/16 [18%]; P=0.002). Children with AN showed significantly higher mean systolic blood pressure, fasting insulin, HOMA-IR, triglycerides, and ALT, as well as lower HDL cholesterol levels compared to those without AN (all P<0.05). They had IR (P<0.001), where hypertension is (P=0.021), while fatty liver is (P=0.001), and abnormal glucose homeostasis is (P=0.003). Conclusion: the result of this study revealed that children and adolescents in Iraq with obesity and acanthosis nigricans obtain increased possibility of insulin resistance and cardiometabolic co-morbidities. AN is an essential clinical sign necessitating early evaluation to allow appropriate interventions.